Application of homotopy perturbation method to the Bratu-type equations - Feng, Xinlong; He, Yinnian; Meng, Jixiang (Topological Methods in Nonlinear Analysis, 2008)
A new algorithm is presented forsolving the Bratu-type equations. The numerical scheme based onthe homotopy perturbation method is deduced. Two boundary valueproblems and an initial value problem are given to illustrateeffectiveness and convenience of the proposed scheme. Our resultsagree very well with the numerical solutions showing that thehomotopy perturbation method is a promising method.